ANALISA KANDUNGAN TIMBAL (Pb) DAN TEMBAGA (Cu) YANG TERDAPAT PADA KERANG DARAH (Anadara granosa) DI PERAIRAN MUARA BADAK - Rahma, Siti; Hariani, Nova; Sudrajat, Sudrajat (BIOPROSPEK: Jurnal Ilmiah Biologi, 2016)
Which aims to determine the levels of heavy metals Pb and Cu in water, sediments and blood clam (Anadara granosa) in Muara Badak. Sampling using purposive sampling method with 3 stations and each station repeated twice. Levels of heavy metals Pb and Cu were measured using Atomic Absorption Spectrophotometer (AAS). The results showed that the levels of heavy metals Cu and Pb in water, sediments and blood clams in Muara Badak as follows: Pb in water ranging between 0,204 – 0,376 ppm and Cu 0,033 to 0,035 ppm, sediment metal content of Pb 0,212 to 0,285 ppm and Cu 0,010 to 0,113 ppm, on blood clams Pb 0,201 to 0,258 ppm and Cu 0,066 to 0,078 ppm. Based on quality standards of heavy metal level Pb and Cu on blood clam did not exceed the threshold of quality standards yet in accordance with SNI No. 7387: 2009 is 1,5 ppm and Department of Health Republic Indonesia No. 0375/B/SK/1989 is 20 ppm